The impact of research in education an international perspective - Levin, Benjamin; Qi, Jie; Sohn, Jacqueline; Edelstein, Hilary (Policy Press, 2013)
This much-needed, original book analyzes efforts and systems in nine countries to mobilize research knowledge, describing the various factors that support or inhibit that work to provide an unprecedented view of the way education research is produced and shared